Cognitive structure of students through socratic questioning in algebra - Bimantara, Abdul Rauf; Sugiatno, Sugiatno; Kusumastuti, Nilamsari (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study investigates the impact of Socratic questioning on students' cognitive structures in learning quadratic equations. By examining different levels of cognitive engagement, this research aims to explore how structured questioning can enhance students' mathematical reasoning and problem-solving abilities.Method: A descriptive-exploratory approach was applied, involving 12th-grade students as participants. Data collection consisted of written tests and semi-structured interviews, which were designed to assess students’ cognitive development across Bloom’s taxonomy: remembering, understanding, applying, analyzing, evaluating, and creating. The students' responses were analyzed to determine patterns in their cognitive engagement.Findings: The results indicate strong performance in lower-order thinking skills, with high scores in remembering (100 percent), understanding (91.66 percent), and applying (86 percent). However, challenges remain in higher-order thinking skills, particularly in analyzing (75 percent), evaluating (80 percent), and creating (72 percent). The study reveals that Socratic questioning effectively strengthens foundational knowledge, comprehension, and application skills, but additional support is required to improve students' abilities in higher-order cognitive processes.Significance: These findings highlight the potential of Socratic questioning as an instructional strategy that fosters deeper learning in mathematics. The study recommends incorporating reflective exercises, targeted mentoring, and extended practice to further enhance students’ cognitive development. By addressing gaps in higher-order thinking, this research contributes to the development of more effective student-centered teaching approaches, aligning with the evolving demands of 21st-century education.